Evaluation of integrated ammonia recovery technology and nutrient status with an in-vessel composting process for swine manure. (December 2017) - Kim, Jung Kon; Lee, Dong Jun; Ravindran, Balsubramani; Jeong, Kwang-Hwa; Wong, Jonathan Woon-Chung; Selvam, Ammaiyappan; Karthikeyan, Obuli P.; Kwag, Jung-Hoon
Highlights: The integration of two process is a good strategy for swine manure management. The final compost from 65% initial moisture content treatment has well matured. A considerable amount of ammonium nitrogen recovered through a condensation process. Future study is needed on recovered ammonium nitrogen used as a liquid fertilizer. Abstract: The study investigated the effect of different initial moisture (IM) content (55, 60, 65, and 70%) of composting mixtures (swine manure and sawdust) for the production of nutrient rich manure, and the recovery of ammonia through a condensation process using a vertical cylindrical in-vessel composter for 56 days. The composting resulted in a significant reduction in C:N ratio and electrical conductivity (EC), with a slight increase in pH in all products. The NH3 were emitted notably, and at the same time the NO3 − -N concentration gradually increased with the reduction of NH4 + -N in the composting mixtures. The overall results confirmed, the 65% IM showed the maximum nutritional yield, maturity and non-phytotoxic effects ( Lycopersicon esculentum L.), with the results of ideal compost product in the following order of IM: 65% > 60% > 70% > 55%. Finally, the recovered condensed ammonia contained considerable ammonium nitrogen concentrations and could be used as fertilizer.